2013
DOI: 10.1002/adhm.201300034
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Dependent Anticancer Drug Release from Silk Nanoparticles

Abstract: Silk has traditionally been used as a suture material because of its excellent mechanical properties and biocompatibility. These properties have led to the development of different silk-based material formats for tissue engineering and regenerative medicine. Although there have been a small number of studies about the use of silk particles for drug delivery, none of these studies have assessed the potential of silk to act as a stimulus-responsive anticancer nanomedicine. This report demonstrates that an aceton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
259
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 217 publications
(281 citation statements)
references
References 33 publications
(62 reference statements)
20
259
1
1
Order By: Relevance
“…SF-based delivery carriers often show drug release characteristics that are governed mostly by solubilisation or degradation of the SF [6]. For the present case, the degradation of SF reduced the sphere size as shown in Section 3.2, affecting the emission properties of NDs on the encapsulated spheres which was investigated during the drug release.…”
Section: Fluorescence Variation With Drug Releasementioning
confidence: 85%
See 3 more Smart Citations
“…SF-based delivery carriers often show drug release characteristics that are governed mostly by solubilisation or degradation of the SF [6]. For the present case, the degradation of SF reduced the sphere size as shown in Section 3.2, affecting the emission properties of NDs on the encapsulated spheres which was investigated during the drug release.…”
Section: Fluorescence Variation With Drug Releasementioning
confidence: 85%
“…Furthermore, drug carriers are expected to stay in the blood for an extended period of time and then accumulate at diseased sites [4]. Current studies [1,3,5,6] have identified that nanoparticles (NPs) not only have the ability to be used as targeted drug delivery platforms but they can also overcome drug resistance through the enhanced permeation and retention (EPR) effect [6]. For NP based drug delivery systems [5], the EPR effect facilitates the deposition of nanoparticles at the tumour site due to the tumour's leaky vasculature, abnormal growth and lack of an effective lymphatic drainage [5,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[37][38][39][40][41][42] As a drug carrier, the SF molecules possess controllability of their degradation under in vitro and in vivo, which can be regulated by changing its size, crystallinity, molecular weight, and degree of cross-linking. 43,44 The hydrophobic amino acid residues in SF molecules, such as alanine, glycine, and tyrosine, can enhance the entrapping of curcumin and 5-FU through hydrophobic interaction and π-π packing, which increase the loading efficacy of the binary drug carrier. Besides, the hydrophilic amino acid residues in SF molecules, such as serine, aspartic acid, and glutamate, increase their water solubility and induce the formation of nanoparticles in aqueous solutions.…”
mentioning
confidence: 99%